(untitled) (PJDOL, 2023)
The main objective of the study was to collect the information or data on issues, problems, challenges and support in accessing technologies for individual with disabilities. The second objective of the study was about the delivery of content, not approachable educational technology that is open source in open and distance education and instructional design. A survey was conducted in Allama Iqbal Open University (AIOU) and formal universities where the disabled students were enrolled.